4x-3y=36

Subtract 4x from both sides of the equation.

-3y=36-4x

Divide each term in -3y=36-4x by -3.

-3y-3=36-3+-4x-3

Cancel the common factor of -3.

Cancel the common factor.

-3y-3=36-3+-4x-3

Divide y by 1.

y=36-3+-4x-3

y=36-3+-4x-3

Simplify each term.

Divide 36 by -3.

y=-12+-4x-3

Dividing two negative values results in a positive value.

y=-12+4×3

y=-12+4×3

y=-12+4×3

The given equation y=-12+4×3 can not be written as y=kx2, so y doesn’t vary directly with x2.

y doesn’t vary directly with x

Find the Quadratic Constant of Variation 4x-3y=36